THE EFFECT OF CONSUMPTION, EXPORT AND IMPORT ON NORTH SUMATRA REGIONAL ECONOMIC GROWTH - Utami, Ayudya (SEAN Institute, 2020)
Economic growth is one indicator as a measure of the progress of economic development in a country or region. Economic growth is defined as the development of activities in the economy that causes goods and services produced in the community to increase and the prosperity of the community to increase. This study aims to determine the effect of consumption, exports and imports on the regional economic growth of North Sumatra. This study uses secondary data obtained directly from the Central Statistics Agency and related agencies or agencies. The analysis used is descriptive quantitative with multiple linear analysis model. In this study using Eviews 8.0 as an estimation tool. The results of the research conducted indicate that consumption has a negative and significant effect on economic growth in North Sumatra with a significance value of 0.0000 which is smaller than the 5% significance level. Exports have a positive and significant effect on economic growth in North Sumatra with a significance value of 0.0000 which is smaller than the 5% significance level. Imports have no effect on economic growth in North Sumatra with a significance value of 0.8300 which is greater than the 5% significance level, and consumption, exports and imports have a significant effect on economic growth in North Sumatra. Then there is a relationship between consumption, exports and imports with economic growth of 78.9% and another 21.1% is explained by other factors not mentioned in this model.